PENGARUH KNOWLEDGE MANAGEMENT DAN ORGANIZATIONAL LEARNING TERHADAP KINERJA ORGANISASI MELALUI INOVASI SEBAGAI VARIABEL INTERVENING - Rizqa Afqarina; Fereshti Nurdiana Dihan (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
This study entitled as The Impact of Knowledge Management and Organizational Learning on Organizational Performance through Innovation as an Intervening Variable (Case Study on Grand Inna Malioboro Hotel). The purpose of this study is to determine the relationship between knowledge management, organizational learning, innovation, and organizational performance. The samples used in this study are employees who have positions as supervisor, officer, manager, and executive with the number of sample returned is 60 respondents. Data analysis techniques used in this study are Structural Equation Modeling (SEM). The result of this study prove that: (1) There is a significant positive relationship between knowledge management and innovation. (2) There is a significant positive relationship between organizational learning and innovation. (3) There is a positive not significant relationship between knowledge management and organizational performance. (4) There is a positive not significant relationship between organizational learning and organizational performance. (5) There is a significant positive relationship between innovation and organizational learning. (6) The role innovation mediates the relationship between knowledge management and organizational performance. (7) and the role innovation mediates the relationship between organizational learning and organizational performance.